2014
DOI: 10.5152/tjbh.2014.2197
|View full text |Cite
|
Sign up to set email alerts
|

Breast Carcinosarcomas

Abstract: Objective: Carcinosarcomas of the breast are rare and aggressive breast tumors. The optimal treatment strategies and the classification of these difficult to diagnose tumors are not clear in the literature due to their very low incidence. In this study, we aimed to evaluate patients who were operated on for breast carcinosarcoma and discuss the current literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 29 publications
(30 reference statements)
1
17
0
Order By: Relevance
“…Our study showed that the 4-year BCSS rate and OS rate of carcinosarcoma was 49.6% and 46.2%, respectively. This poor clinical outcome was similar to other reports [ 8 , 13 ]. Some studies further conducted a comparison of breast carcinosarcoma with other subtypes of breast metaplastic carcinoma.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed that the 4-year BCSS rate and OS rate of carcinosarcoma was 49.6% and 46.2%, respectively. This poor clinical outcome was similar to other reports [ 8 , 13 ]. Some studies further conducted a comparison of breast carcinosarcoma with other subtypes of breast metaplastic carcinoma.…”
Section: Discussionsupporting
confidence: 92%
“…Due to the specific histologic feature, breast carcinosarcoma may have different biological characteristics when compared with IDC. Because of the rarity of breast carcinosarcoma, previous publications about this disease were a few small sample size retrospective analyses [ [8] , [9] , [10] , [11] , [12] , [13] , [14] ] and a few case reports [ [15] , [16] , [17] , [18] , [19] , [20] ]. From these limited studies, it appears that breast carcinosarcoma is always aggressive, poorly differentiated, and hormone receptor-negative [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization’s histological classification for tumors of the breast classifies metaplastic carcinoma into pure epithelial metaplastic carcinomas, squamous cell carcinoma, adenocarcinoma with spindle cell metaplasia, adenosquamous carcinoma, mucoepidermoid carcinoma, or mixed epithelial/mesenchymal metaplastic carcinomas. The mean age at diagnosis lies between the fourth and fifth decades of life (i.e., the perimenopausal age group) [ 8 , 9 ]. The median tumor size is reported to range from 3.4 to 5.7 cm in various series [ 10 - 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mixed epithelial-mesenchymal carcinoma is further classified into carcinomas with chondroid metaplasia, carcinomas with osseous metaplasia, and carcinosar-coma (5,9,10). The histological origin of breast carcinosarcoma remains unclear, but it may be derived from stem cells with biphasic differentiation, from metaplasia of myoepithelial cells and myofibroblasts, or from preexisting fibroadenomas and phyllodes (3,14). Most evidence suggests that tumors are of myoepithelial origin with both carcinomatous and sarcomatous characteristics on histopathology (7,11,13).…”
mentioning
confidence: 99%
“…The clinical symptoms of breast carcinosarcoma are similar to invasive ductal carcinoma, and include the presence of a large painful mass, nipple discharge, nipple depression, and skin ulceration (7,8,12,14). One study reported a case of carcinosarcoma presenting as a breast abscess (15).…”
mentioning
confidence: 99%